1960
DOI: 10.1113/jphysiol.1960.sp006585
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase and antidiuretic activity in urine of man

Abstract: Until recently the action of the antidiuretic hormone has been described as restoring 'water balance by promoting the reabsorption of the osmotically free water left by the distal reabsorption of Na. Under the action of the hormone this water is reabsorbed; in its absence this water is excreted' (Smith, 1956). Wirz (1956) has suggested an explanation of the mechanism of water reabsorption. He, and later Gottschalk & Mylle (1959), showed by micropuncture study in the rat that fluid in the first half of the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

1961
1961
1973
1973

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 8 publications
2
22
0
1
Order By: Relevance
“…of oxytocic activity) shows no activity, a result in agreement with those of other observers (Cross, Dicker, Kitchin, Lloyd & Pickford, 1960 Hyaluronida.e concentration. As found previously (Dicker & Eggleton, 1960), hyaluronidase could be detected in the urine at a relatively slow rate of flow, and its concentration was then more or less quantitatively related to rate of flow, as may be seen in Figs. 3 and 5.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…of oxytocic activity) shows no activity, a result in agreement with those of other observers (Cross, Dicker, Kitchin, Lloyd & Pickford, 1960 Hyaluronida.e concentration. As found previously (Dicker & Eggleton, 1960), hyaluronidase could be detected in the urine at a relatively slow rate of flow, and its concentration was then more or less quantitatively related to rate of flow, as may be seen in Figs. 3 and 5.…”
Section: Resultssupporting
confidence: 59%
“…Repeated measurements of the same solution indicated that the mean error of a single determination was about + 2 %, or + 5 % if the concentration was less than 250 m-osmole/l. Hyaluronidase was determined by change in viscosity of hyaluronic acid (Dicker & Eggleton, 1960). The molecular weight of the carbowax used in concentrating the urine samples (15,000-20,000) is close to the pore size of the Visking tubing in which it was contained, and with some batches slight leakage occurred through the tubing.…”
Section: E S Dicker and M Grace Eggleton Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to form a hypertonic urine according to the 'counter current multiplier' theory may be affected by several factors, including the length of the loops of Henle, the plasma urea concentration and the ability of the kidney to respond to antidiuretic hormone . However, and Dicker & Eggleton (1960) consider that the latter factor is not important in this respect. Histological examination of the kidney of Setonix shows that growth during the first 100 days after birth consists mainly of the formation of new nephrons with a subsequent elongation of these tubules in the older animals.…”
Section: Discussionmentioning
confidence: 99%
“…The buffer system was the citric-acid-phosphate buffer (Mcllwaine, 1921). When necessary, samples of supernatant fluids from tissues were concentrated by dialysis against carbowax 20 M (Dicker & Eggleton, 1960, 1961.…”
Section: Methodsmentioning
confidence: 99%